Annual Plan 2004-05 Revised Outlay 2004-05 - Planning Commission (Planning Commission, 2004)
State Plan Advisers may kindly refer to D.O. Letter No. M- 13011/1/2003-SP.CO./DCH/11/2004/649 dated 23.8.2004 from Deputy Chairman, Planning Commission addressed to Chief Ministers regarding finalisation of Annual Plan 2004-05 of States and Union Territories(UTs) circulated vide letter No. M- 13011/1/2004-SP-Co dated 26.08.2004, copy of which is enclosed, for ready reference. The deadline for receipt of Annual Plan 2004-05 proposals of States and UTs, as indicated in this letter, was 30th September,: 2004 and issue of approval letters was scheduled to start from 15th October, 2004. State Plan Advisers are requested-to kindly ensure that Annual Plan 2004-05 proposals of the States/UTs under their charge are received by them early.
Planning Commission State Plans Division